Amine Based Corrosion Inhibition Analysis On Suram West Area – Petapahan And Kotabatak – Petapahan API 5L Grade B Pipeline - Syahputra, Darma Reza; Suyitno, Suyitno (Sekolah Tinggi Teknologi Adisutjipto, 2019)
In Petapahan, Kotabatak, and Suram West Area Gathering Station, Hot water shipping system is used as oil shipping system for production. This fluid is highly corrosive and there is no corrosion protection by corrosion inhibition available for this pipeline until now, hence multiple leaks occurred massively since several years ago. This thesis focused in analysis of amine-based corrosion inhibitor with several concentration variations against API 5 L Grade-B corrosion rate in waxy oil fluid inside Petapahan - Kotabatak and Suram West Area ? Petapahan Pipeline. Concentration variation that used are 0, 20, 40, 60, 80 and 100 ppm while pipe has outside diameter of 4.5 in (114.3 mm) and thickness of 0.237 in (6.02 mm). Corrosion rate analysis conducted using potentiodynamic polarization (Tafel plot). For Petapahan ? Kotabatak fluid, corrosion rates are 10.51, 15.85 and 46.60 mpy at temperature of 30, 40 and 50 C. 20 ppm amine-based inhibitor injection at 50 C showed lowest corrosion rate at 46.10 mpy. While for Suram West Area fluid, corrosion rates are 12.19, 12.41 and 29.85 mpy at temperature of 30, 40 and 50 C. 60 ppm amine-based inhibitor injection at 50 C showed lowest corrosion rate at 26.92 mpy. Hardness test conducted also showed a drop in HVN no from 48.39 to 13.74